Foreign funding of U.S. higher education relates to sanctioning of scholars and antisemitism - Bass, Michael; Ross, Alexander Reid; Wolfson, Ben; Finkelstein, Joel; Yanovsky, Sonia; Finkelstein, Danit; Stevens, Sean T.; Honeycutt, Nathan; Paresky, Pamela; Feinberg, Ayal; Small, Charles Asher; Jussim, Lee (Frontiers in Social Psychology, 2024)
We examined relations between foreign funding of U.S. colleges and universities and campus political developments. Seven studies investigated associations between foreign funding and campus liberal democratic norms, specifically, deterioration of free speech and academic freedom, and presence of antisemitism. Study I found that 349 colleges and universities received a total of almost 18 billion from foreign sources between 2014 and 2019. Study II examined relationships of foreign funding to campus deplatforming of speakers and punitive actions for speech protected by academic freedom. Main results were: 1. overall foreign funding was not strongly related to campus speech outcomes; 2. higher levels of deplatforming and speech punishment occurred on campuses that received funding from member states of the Organisation of Islamic Cooperation and from authoritarian countries. Study III found weak evidence that foreign funding was associated with college students’ reported exposure to antisemitic and anti-Zionist tropes. After demonstrating substantial correlations among three national measures of antisemitic incidents (Study IV), Study V found that foreign funding provided by member countries of the Organisation for Islamic Cooperation or by authoritarian countries was associated with elevated levels of campus antisemitism and anti-Zionist incidents. Studies VI and VII found that antisemitic incidents on campus were associated with antisemitic incidents across the country. This research highlighted troubling possibilities about the potential role of foreign funding in higher education that deserve further investigation.